Why are some children under 24 months still undernourished in urban and peri-urban Vientiane? A mixed-methods study - Kethmany Ratsavong; Dirk Essink; E. Pamela Wright; Somphou Sayasone; Sengchanh Kounnavong; Jacqueline E. W. Broerse (PLoS ONE, 2026)
Child undernutrition remains a significant public health challenge in many low and middle-income countries (LMICs), including Lao PDR, where high levels persist even in urban areas with generally available and accessible food. This study aimed to explore factors underlying the persistently high rates of undernutrition among young children in urban (Saysetha) and peri-urban (Pakgneum) districts of the Vientiane Capital in Lao PDR. A cross-sectional survey employed a sequential explanatory mixed-methods approach, combining a structured questionnaire of 333 mother–child pairs for quantitative analysis with semi-structured interviews of 47 caregivers for qualitative insights. The prevalence of malnutrition among children under 24 months in Vientiane Capital was 27.3% for stunting, 4.2% for wasting, 14.4% for underweight, and 5.11% for overweight. Multiple logistic regression was applied to identify factors associated with malnutrition, while qualitative data were thematically analyzed. The principal findings revealed that, beyond food access, the quality of caregiving and, critically, caregivers’ capacity to translate nutrition knowledge into effective practices distinguished well-nourished from undernourished children. Caregivers of better-nourished children obtained health and nutrition information from diverse sources, whereas those of undernourished children relied mainly on health services. In conclusion, strengthening practical nutrition communication in various methods and channels, such as through videos and demonstrations, and enhancing caregivers’ ability to apply nutritional knowledge, are central to improving child nutritional outcomes in urban and peri-urban settings in Lao PDR.